2018
DOI: 10.1002/pssa.201700775
|View full text |Cite
|
Sign up to set email alerts
|

Omnidirectional Reflector with Total Internal Reflective Interface for Light Extraction Enhancement of Solid‐State Light Source

Abstract: Light extraction efficiency is key to the performance of solid-state light sources such as the light-emitting diode. The reflectance of the bottom mirror has a significant impact on the light extraction efficiency because a large difference in the refractive index between the light source and air leads to multiple internal reflections and optical loss. Therefore, efficiency can be drastically improved with even a slight increase in the bottom mirror reflectance. This paper focuses on wide angular light inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Thus, depositing a reflector onto p -GaN in order to reflect photons emitted downward can significantly enhance the LEE of the FCLEDs [38]. It has been reported that various reflectors, such as metallic mirrors and dielectric distributed Bragg reflectors (DBRs), have been used to enhance the LEE of FCLEDs [39,40,41,42]. In addition, highly reflective DBRs are also important for realizing high performance vertical-cavity surface emitting laser [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, depositing a reflector onto p -GaN in order to reflect photons emitted downward can significantly enhance the LEE of the FCLEDs [38]. It has been reported that various reflectors, such as metallic mirrors and dielectric distributed Bragg reflectors (DBRs), have been used to enhance the LEE of FCLEDs [39,40,41,42]. In addition, highly reflective DBRs are also important for realizing high performance vertical-cavity surface emitting laser [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…over a 2.5 GHz to 3.5 GHz frequency range with 13.5 ± 1.0 dB gain. The maximum output power density of 4.15 W/mm is comparable with commercially available GaN HEMTs e.g., Wolfspeed CGH6008D 3.8 W/mm (Durham, NC, USA) [40], Qorvo TGF2023-2-01 4.8 W/mm) (Greensboro, NC, USA) [41].…”
Section: Design and Fabrication Of The On Microwave Power Amplifier Umentioning
confidence: 56%
“… is the incident angle to the reflector. The causal relationship between the microstructure and reflectance of the backside mirror has been already reported with the optical simulation of the LEE [21].…”
Section: Simulationmentioning
confidence: 58%
“…Total internal reflective omnidirectional reflector (TI-ODR) which is designed to utilize TIR of wide angular incident light by low-index thick layer was developed. The angular integrated reflectance of TI-ODR reached to 99.7% and indicated LEE enhancement effect of solid-state lighting devices [21]. However, since the multi-layer structure was optimized to maximize optical property, the other properties are insufficient for device and application.…”
Section: Introductionmentioning
confidence: 99%